Establishment of a dendritic cell differentiation system faithfully recapitulating multiple DC subsets in autoimmune disease - Siqi Bi; Ye Tian; Yiping Le; Honglin Li; You Wang; Can Liu; Haibo Zhou (Tissue and Cell, 2026)

Multiple ecological mechanisms drive effects of fertilization and herbivore exclusion on species richness in an alpine grassland community - Wei Zhao; Shaohao Bang; Zhenzhen Pan; Ruibing Wang; Huan Chen; Xiaolong Zhou; Defei Liang; Honglin Li; Ning Chen; Shiting Zhang; Zhengwei Ren (Agriculture, Ecosystems & Environment, 2026)

A high-throughput strategy for screening umami peptides from Chouguiyu based on peptidomics and machine learning-assisted molecular simulation - Sitong Lyu; Shichao Xuan; Fan Yang; Honglin Yu; Di Meng; Jianqing Zhou; Cristabelle De Souza; Zhe Zhang; Tongjie Liu; Huaxi Yi; Qingjuan Tang; Lanwei Zhang; et al. (Food Research International, 2026)

Addition of small-molecule polysaccharides and polyols improves the porous microstructure and quality of freeze-dried strawberry slices enriched with Lactobacillus plantarum - Feifei Yang; Yiyang Qi; Xiyun Sun; Hongwei Xiao; Xuemei Gao; Yulong Wu; Shoujiang Chen; Honglin Zhang; Feng Zhou; Haiou Wang; Huichang Wu (Food Chemistry, 2026)

Divergent effects of fertilization and grazing exclusion on species diversity in alpine grasslands - Zhengwei Ren; Wei Zhao; Zhenzhen Pan; Shaohao Bang; Ruibing Wang; Huan Chen; Defei Liang; Honglin Li; Dexiecuo Ai; Renyi Zhang; Ning Chen; Xiaolong Zhou (Ecological Engineering, 2026)

Comprehensive investigations reveal high occurrence of tet(X) in blaNDM-positive Acinetobacter spp. from Chinese cattle production systems - Weiwei Wang; Qing Wang; Yanhua Qiu; Guonian Dai; Bing Li; Honglin Lin; Yaxin Zhou; Jiyu Zhang (International Journal of Food Microbiology, 2026)

Physiological and transcriptomic responses of Heterosigma akashiwo to nitrogen deficiency and urea utilization - Bin Han; Honglin Chen; Xinxia Qi; Nanjing Ji; Yue Pan; Xiaotong Cheng; Lingjie Zhou; Xin Shen (Harmful Algae, 2026)

Recruitment is the key process that improves trait-based predictions of tree range shifts - Yujun Feng; Yi Zheng; Jin Yin; Yue Bin; Pengcheng He; Dongxu Zhang; Honglin Cao; Ying Lei; Boao Zhang; Jinggang Zhou; Bo Cui; Wanhui Ye; et al. (Forest Ecology and Management, 2026)

Petrogenesis and tectonic significance of the Maliqing gabbros in the eastern margin of Lanping Basin, SW China: geochemical, Sr–Nd–Hf isotopic compositions, and geochronological evidence - HongLin Zhou; Wei Wang; JiaHui Zhang; QingQing Yang; ZhengQiao Li; ZhiPeng Xie; ChuanDong Xue (Acta Geochimica, 2026)

Probiotic fermented Dendrobium beverages: Effect of co-probiotic strains on the flavor composition and bioactive constituents. - Yixia Zhou; Luqi Qin; Honglin Chen; Ziyi Chen; Jing Sun; Jia Yao; Bei Fan; Jiameng Liu (Food Research International, 2026)

Adaptive strategies of the harmful alga Heterosigma akashiwo to low salinity: rapid stress responses and long-term metabolic remodeling - Qiuping Li; Bin Han; Yinghao Wang; Xinxia Qi; Nanjing Ji; Xiaotong Cheng; Honglin Chen; Lingjie Zhou; Xin Shen (Harmful Algae, 2026)

Nano zero-valent iron-modified biochar regulates soil carbon mineralization and stability across aggregates in alpine degraded grassland - Yao Li; Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Feida Sun; Jinchao Gong; Shijie Zhou; Zhouwen Ma; Chengjing Wu; Lin Liu; Ran Xue; Yue Xiu; et al. (Soil Ecology Letters, 2026)

Slope aspect modulates fertilization impacts on PLFA-based soil microbial community structure but not on diversity in a degraded alpine grassland under restoration - Qiang Zhang; Yunfei Xing; Xiaoli Wang; Jianjun Shi; Chunhui Zhang; Huakun Zhou; Honglin Li; Xinquan Zhao; Yushou Ma (Plant and Soil, 2026)

Coordinated pathways to a low-carbon, healthy, and equitable food system in China - Xinxian Qi; Zemiao Liu; Yiqi Zhou; Honglin Zhong; Pan He; Xianjin Huang; Laixiang Sun; Kuishuang Feng; Hong Yang; Julian R. Thompson; Yanfeng Di; Taiyang Zhong; et al. (Science Bulletin, 2026)

Fertilization and herbivore exclusion promote more deterministic processes in plant community assembly on the Qinghai–Tibet Plateau - Wei Zhao; Shaohao Bang; Zhenzhen Pan; Ruibing Wang; Huan Chen; Dexiecuo Ai; Xiaolong Zhou; Honglin Li; Ning Chen; Shiting Zhang; Zhengwei Ren (Oecologia, 2026)

Rapid Nutritional Screening and Short-Term Prognosis in Advanced Schistosomiasis: A Prospective Cohort Study - Honglin Jiang; Xinting Cai; Mao Zheng; Benjiao Hu; Meng Xia; Qingwu Jiang; Yibiao Zhou (Acta Parasitologica, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Impedance-based electrochemical equilibrium of two referenced solid electrolyte oxygen sensors in liquid LBE - Honglin Zhou; Haicai Lyu; Zhen Yang; Jiyao Wang; Fang Liu; Xingyan Zhou; Ruixian Liang; Huiping Zhu; Shengfei Wang; Zhangpeng Guo; Fenglei Niu (Annals of Nuclear Energy, 2026)

A fluorescence biosensor based on upconversion nanoparticles and metal organic frameworks for multiresidue detection and enrichment of neonicotinoid pesticides - Huan Yun; Honglin Li; Zijie Dou; YuHao Zhang; Ting Guo; Ying Zhou; Hongyuan Zhou; Liang Ma; Xiaozhu Liu (Food Chemistry, 2026)

Culinary secrets of sweet potatoes: A metabolomic perspective - Jiahao Zhang; Wenhao Zhong; Bolin Wei; Biao Zhao; Yanyue Liang; Yihang Jiang; Tongxian Zhou; Jiatong Han; Zixian Wu; Honglin Yang; Shunhong Feng; Wenyi Wang; et al. (Food Chemistry, 2026)

Carbon sequestration patterns in the Yellow River Basin of China are governed by the vegetation structural dynamics - Zhongen Niu; Honglin He; Mengyu Zhang; Tingting Liu; Pan Li; Tao Zhou; Lili Feng; Yan Lv (Journal of Environmental Management, 2025)

Correlation between atmospheric boundary layer height and Concentration of dust aerosols in Taklimakan desert - Congzhen Zhu; Mingzhong Wang; Lu Meng; Ali Mamtimin; Fan Yang; Chenlong Zhou; Honglin Pan; Jiantao Zhang (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Dietary Houttuynia cordata Thunb attenuates redox imbalance and inflammation possibly induced by heat stress in dairy cows associated with altered fecal microbiota and metabolomics profile - Lunjie Feng; Hongyu Yi; Zhaoxi Xie; Pan Zhou; Yong Zhang; Ling Cheng; Shuai Chen; Liwen Chen; Chengquan Jiang; Hui Diao; Honglin Yan (Tropical Animal Health and Production, 2025)

Thermally aged PET microplastics disrupt methanogenic syntrophy via toxic leachates: Microbial assembly dynamics unravel biotoxicity in anaerobic digestion - Honglin Zhou; Xin Kong; Lei Chen; Xumiao Mao; Delin Yin; Jin Yuan; Yifeng Zhang (Journal of Hazardous Materials, 2025)

Investigation of the solid-state fermentation of Astragalus membranaceus residue with Cordyceps militaris: effects on phenolic profile and in vitro neuroprotective activity - Qiaona Wang; Lu Li; Liyun Hu; Ying Cao; Yutong Cao; Jiayi Gao; Honglin Zhang; Feng Zhou; Yulong Wu; Shengjie Li; Renlei Wang (Food Chemistry, 2025)

Physiological and molecular responses of the dinoflagellate Gymnodinium impudicum to phosphorus deficiency: Insights into dissolved organic phosphorus utilization strategies - Yujiao Chen; Mingyang Xu; Yinghao Wang; Honglin Chen; Xiaotong Cheng; Nanjing Ji; Lingjie Zhou; Song Sun; Xin Shen (Algal Research, 2025)

Electrostatic interaction strategy stabilizes the crystal structure in ultra-high Ni cathode - Jianlong Wang; Honglin Yan; Cheng Wei; Yuan Ha; Weidong Zhu; Lu Li; Chaoyi Zhou; Qianxin Xiang; Zhimin Li; Yue Hao (Chemical Engineering Journal, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

A visible-light-driven polythiophene/MgAl-LDH@CuxS photocathode enhanced the generation of reactive oxygen species for water disinfection - Mingyu Wang; Honglin Kuang; Lu Zhou; Mengru Shan; Sihao Jiang; Danying Ma; Shiwen Lv; Yanqing Cong; Yingqi Song; Yi Zhang (Chemical Engineering Journal, 2025)

The unique transmembrane protein NbTMP2 (NBO_555g0004) of Nosema bombycis contributes to host infection - Shaogang He; Shiyi Zheng; Yuanke Hu; Zhonghua Yang; Honglin Zhu; Bin Yu; Junhong Wei; Guoqing Pan; Zeyang Zhou; Chunfeng Li (Journal of Invertebrate Pathology, 2025)

Deciphering the inhibitory mechanisms of polystyrene microplastics on thermophilic methanogens from the insights of microbial metabolite profiling and metagenomic analyses - Xuejiao Qiao; Xin Kong; Honglin Zhou; Xiaojun Fan; Jin Yuan; Yifeng Zhang (Journal of Hazardous Materials, 2025)

LVR: A language and vision fusion method for rice diseases segmentation under complex environment - Tianrui Zhao; Honglin Zhou; Miying Yan; Guoxiong Zhou; Chaoying He; Yang Hu; Xiaoyangdi Yan; Meixi Pan; Yunlong Yu; Yiting Liu (European Journal of Agronomy, 2025)

Deformation and Cracking Evolution Mechanism of Surrounding Rock in Deep Clastic Rock Tunnels: A Scaled-Down Excavation Experimental Study - Feiyan Wang; Xia-Ting Feng; Yangyi Zhou; Xiaojun Yu; Chengxiang Yang; Bentong Sun; Fudong Li; Honglin Luo (Rock Mechanics and Rock Engineering, 2025)

Gold mineralization in the hydrothermal field at the termination of a detachment fault: A case study of the Tianxiu Vent Field - Ming Yang; Yejian Wang; Sven Petersen; Zhongyan Qiu; Honglin Li; Peng Zhou; Yiyang Cai; Xing Yu; Matthias Frische; Jiqiang Liu; Xiqiu Han (Mineralium Deposita, 2025)

Coupling relationship of the Mississippi Valley-type zinc‑lead deposit and hydrothermal dolostone: Its role in metallogeny - Aiying Wei; Yiwen Ju; Yingchao Liu; Shuya Zhang; Huaikun Ma; Honglin Zhou; Dong Pan; Chuandong Xue (Earth-Science Reviews, 2025)

Biochar addition affects the microfood web structure of soil animals: A meta-analysis - Fang Yuan; Xue Hu; Wang Shiping; Li Ma; Zhonghua Zhang; Lihong Song; Honglin Li; Buqing Yao; Huakun Zhou (CATENA, 2025)

Research on the source of cinnabar excavated from Sanxingdui site in China based on sulphur and mercury isotope analyses - Qinxin Jiang; Guangyi Sun; Honglin Ran; Yu Lei; Chong Wang; Zhenbin Xie; Fei Tang; Jian Yu; Bisu Zhou; Min Shi; Wan Peng; Chenghui Li; et al. (Archaeological and Anthropological Sciences, 2025)

Recent developments on the freeze-thaw stability of Pickering emulsions and its application as nutrient delivery vehicles - Chaosheng Wu; Honglin Chen; Tiannu Zhang; Wei Wang; Longwei Chen; Xiao Feng; Feibai Zhou; Xiaozhi Tang (Food Hydrocolloids, 2025)

Metagenomic and FT-ICR MS insights into the mechanism for the arsenic biogeochemical cycling in groundwater - Honglin Jiang; Xianjun Xie; Junxia Li; Zhou Jiang; Kunfu Pi; Yanxin Wang (Journal of Hazardous Materials, 2024)

Exploring Novel Fentanyl Analogues Using a Graph-Based Transformer Model - Guangle Zhang; Yuan Zhang; Ling Li; Jiaying Zhou; Honglin Chen; Jinwen Ji; Yanru Li; Yue Cao; Zhihui Xu; Cong Pian (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Application of physicochemical techniques to the removal of ammonia nitrogen from water: a systematic review - Tianhong Zhou; Miao Wang; Honglin Zeng; Rui Min; Jinyi Wang; Guozhen Zhang (Environmental Geochemistry and Health, 2024)

Conditions optimization and mechanistic study of chlortetracycline hydrochloride adsorption by TBAOH-MXene: Prediction results based on backpropagation neural network-genetic algorithm and response surface methodology - Mingrong Lu; Shuju Fang; Yao Zhang; Hongyang Zheng; Honglin Xie; Chunxian Zhou; Xuewen Tan; Wanqin Wu; Guizhen Li (Process Safety and Environmental Protection, 2024)

Response of methanogenic metabolism to polystyrene microplastics at varying concentrations: The trade-off between inhibitory and protective effects in anaerobic digestion - Xuejiao Qiao; Xin Kong; Qirui Che; Honglin Zhou; Jin Yuan; Yifeng Zhang (Journal of Cleaner Production, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

Pioglitazone ameliorates ischemia/reperfusion-induced acute kidney injury via oxidative stress attenuation and NLRP3 inflammasome - Zhenfeng Ye; Jing Zhang; Zhou Xu; Zhangwang Li; Gaomin Huang; Bin Tong; Panpan Xia; Yunfeng Shen; Honglin Hu; Peng Yu; Xiaoqing Xi (Human Cell, 2024)

Short-stranded DNA segment-modulated LAMP/H+ as signal transducer to guide CHA-cooperated amplifiable electrochemical biosensing - Jingjing Ye; Weixiang Huang; Xinyue Jia; Honglin Song; Yifu Zhou; Ruo Yuan; Wenju Xu (Analytica Chimica Acta, 2024)

Reconstructing historical forest spatial patterns based on CA-AdaBoost-ANN model in northern Guangzhou, China - Xin Zhan; Shixiao Yu; Yide Li; Zhang Zhou; Honglin Cao; Guangda Tang (Landscape and Urban Planning, 2024)

Multi-omics analysis of attenuated variant reveals potential evaluation marker of host damaging for SARS-CoV-2 variants - Guangshan Xie; Lin Zhu; Siwen Liu; Cun Li; Xin Diao; Yanhao Zhang; Xiuli Su; Yuanyuan Song; Guodong Cao; Li Zhong; Pui Wang; Xiaojuan Liu; et al. (Science China Life Sciences, 2024)

Hydrothermal alteration of basalts in the ultramafic-associated Tianxiu Vent Field, Carlsberg Ridge - Peng Zhou; Xiqiu Han; Yejian Wang; Xueting Wu; Tong Zong; Xing Yu; Jiqiang Liu; Honglin Li; Zhongyan Qiu (Marine Geology, 2023)

Comparative Analysis of the Expression of Resistance-Related Genes Respond to the Diversity Foliar Pathogens of Pseudostellaria heterophylla - Xiao-Ai Wang; Yanping Gao; Weike Jiang; Lu Wang; Hui Wang; Xiaohong Ou; Yang Yang; Honglin Wu; Lanping Guo; Tao Zhou; Qing-Song Yuan (Current Microbiology, 2023)

Tunable reduced graphene oxide nanofiltration membrane for efficient retention and separation of dye/salt based on molecular interactions - Yu Gao; Yun Zhang; Xiaoming Cai; Hangjing Zhou; Zisong Kong; Xiaolong Ma; Lei Gao; Honglin Tan; Jinming Cai (Journal of Environmental Chemical Engineering, 2023)

Salinization of coastal saline-alkali soil might enhance H2S release by affecting H2S-related bacterial communities - Yufeng Xin; Honglin Zhang; Yu Wu; Peng Sun; Junqing Xie; Ronghua Zhao; Yujie Zhou; Ning Ding; Xinyi Qu; Qing Huang; Na Liu; Xiaohua Qu (Applied Soil Ecology, 2023)

Viperin deficiency promotes dendritic cell activation and function via NF-kappaB activation during Mycobacterium tuberculosis infection - Xinying Zhou; Hui Xu; Qianna Li; Qi Wang; Honglin Liu; Yingqi Huang; Yao Liang; Linmiao Lie; Zhenyu Han; Yaoxin Chen; Yulan Huang; Wenle Zhou; et al. (Inflammation Research, 2023)
Objectives and design Dendritic cells (DCs) are one of the key immune cells in bridging innate and adaptive immune response against Mycobacterium tuberculosis (Mtb) infection. Interferons (IFNs) play important roles in regulating DC activation and function. Virus-inhibitory protein, endoplasmic reticulum-associated, interferon-inducible (Viperin) is one of the important IFN-stimulated genes (ISGs), and elicits host defense against infection. Methods We investigated the effects and mechanisms of Viperin on DC activation and function using Viperin deficient bone marrow-derived dendritic cells (BMDCs) during Mtb infection. Results Viperin deficiency enhanced phagocytic activity and increased clearance of Mtb in DCs, produced higher abundance of NO, cytokine including interleukin-12 (IL-12), Tumor necrosis factor-α (TNF- α ), IL-1 β , IL-6 and chemokine including CXCL1, CXCL2 and CXCL10, elevated MHC I, MHC II and co-stimulatory molecules expression, and enhanced CD4 + and CD8 + T cell responses. Mechanistically, Viperin deficiency promoted DC activation and function through NF-κB p65 activation. NF-κB p65 inhibitor prevented cytokine and chemokine production, and co-stimulatory molecules expression promoted by Viperin deficiency. Conclusions These results suggest that Mtb induced Viperin expression could impair the activation of host defense function of DCs and DC-T cell cross talk during Mtb infection. This research may provide a potential target for future HDT in TB therapy.

A Priori Constrained ACO Method Applied to Three-Dimensional Imaging of Subsurface Electrical Resistivity - Qian Guo; Hai Wang; Jian Bai; Benchao Liu; Honglin Wu; Zhenyu Wu; Zhou He (Geotechnical and Geological Engineering, 2023)

Differences in Intestinal Microbial Composition between Red Claw Crayfish (Cherax quadricarinatus) and Red Swamp Crayfish (Procambarus clarkii) Cultured in Pond - Honglin Chen; Fangfang Liu; Miaofeng Ouyang; Huan Zhou; Bao Lou (Fishes, 2022)
Intestinal microbiota communities participate in several metabolic processes in the host, and are highly correlated to digestion, nutrition, growth, and immunity. However, the intestinal microbiota of aquatic invertebrates is poorly understood, especially in freshwater crayfish. In this study, the intestinal microbiota of two important freshwater economic aquaculture species, the invasive species, the red swamp crayfish (Procambarus clarkii, Pc), and the introduced species, the red claw crayfish (Cherax quadricarinatus, Cq), were investigated. The results showed that the community richness and diversity of Pc were higher than those of Cq, which might be one of the reasons that Pc have stronger environmental adaptability than Cq. Five core phyla were identified in the Pc group, including Proteobacteria (26.92%), Tenericutes (25.73%), Bacteroidetes (25.12%), Firmicutes (14.03%), and RsaHF231 (8.02%), and three phyla were detected in the Cq group, including Tenericutes (67.35%), Proteobacteria (25.98%), and Firmicutes (4.69%). In Pc and Cq groups, Proteobacteria exhibited significant differential abundance between males and females. In addition, Vibrio coralliilyticus were found particularly in the intestine of Cq. This study provides information on intestinal microbiota differences of Pc and Cq, contributing to the development of new dietary formulations and providing significance to future aquaculture.

Soil causes gut microbiota to flourish and total serum IgE levels to decrease in mice - Dongrui Zhou; Na Li; Fan Yang; Honglin Zhang; Zhimao Bai; Yangyang Dong; Mengjie Li; Wenyong Zhu; Zhongjie Fei; Pengfeng Xiao; Xiao Sun; Zuhong Lu (Environmental Microbiology, 2022)
Summary Traditional farm environments induce protection from allergic diseases. In this study, farm environmental factors were classified into three categories, environmental microbes, soil, and organic matter. To explore the impact of soil and environmental microorganisms on gut microbiota and immune function, mice were fed sterilized soil and inhaling microbes, soil microbes, or non‐sterilized soil. Metagenomic sequencing results showed the intake of sterile soil, that is, inhaling a small amount of soil microbes in the air increased gut microbial diversity and the abundance of type III secretion system (T3SS) genes, and decreased serum immune IgE levels induced by 2‐4‐dinitrofluorobenzene (DNFB). The intake of soil microbes increased the abundance of genes involved in the metabolism of short‐chain fatty acids and amino acid biosynthesis. Meanwhile, the intake of soil increased gut microbial diversity, the abundance of T3SS genes and related infectious elements, and genes associated with the metabolism of short‐chain fatty acids and amino acid biosynthesis, and decreased serum IgE levels. Therefore, soil may be useful as a potential ‘prebiotic’ promoting the reproduction and growth of some intestinal microorganisms that harbour bacterial secretion system genes, especially those of T3SS, whose abundance was positively and significantly correlated with innate immune function of mice.

Distance to highway and factory density related to lung cancer death and associated spatial heterogeneity in effects in Jiading District, Shanghai - Na Zhang; Yingjian Wang; Hongjie Yu; Yiying Zhang; Fang Xiang; Honglin Jiang; Yingyan Zheng; Ying Xiong; Zhengzhong Wang; Yue Chen; Qingwu Jiang; Yueqin Shao; et al. (Environmental Science and Pollution Research, 2021)

Changes in distribution and morphology of Tamarix ramosissima nebkhas in an oasis-desert ecotone - Chaofan Li; Fan Yang; Xinqian Zheng; Zhangyong Han; Honglin Pan; Chenglong Zhou; Chunrong Ji (Geosciences Journal, 2021)

Comparison and Analysis of Meteorological Variables Observed from the Glacier Area over the Tianshan Mountains in Kyrgyzstan and China - Honglin Pan; Wen Huo; Kanike Raghavendra Kumar; Ali Mamtimin; Minzhong Wang; Junjian Liu; Chenglong Zhou; Fan Yang; Xinghua Yang (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Novel Peptide Inhibitors of β-Catenin Effectively Suppress the Tumorigenesis of Colorectal Cancer - Honglin Liu; Xingyun Liu; Yuexi Li; Xia Zhou; Xiutao Tan; Bo Niu; Niuliang Cheng; Hailin Liu (International Journal of Peptide Research and Therapeutics, 2021)

MERISTEM ACTIVITYLESS (MAL) is involved in root development through maintenance of meristem size in rice - Wei Jiang; Shaoli Zhou; Honglin Huang; Huazhi Song; Qinglu Zhang; Yu Zhao (Plant Molecular Biology, 2020)

Dual-Emitting N/S-Doped Carbon Dots-Based Ratiometric Fluorescent and Light Scattering Sensor for High Precision Detection of Fe(III) Ions - Zhiyan Chen; Xueqin Xu; Dongling Meng; Honglin Jiang; Yun Zhou; Shouai Feng; Zhao Mu; Yaling Yang (Journal of Fluorescence, 2020)

Discovery of a natural fluorescent probe targeting the Plasmodium falciparum cysteine protease falcipain-2 - Lili Zhu; Lei Shan; Junsheng Zhu; Li Li; Shiliang Li; Liyan Wang; Jiawei Wang; Shoude Zhang; Hongchang Zhou; Weidong Zhang; Honglin Li (Science China Life Sciences, 2020)

Evaluation of wind erosion in the Tarim Basin based on parameter localization - Chenglong Zhou; Fan Yang; Wen Huo; Honglin Pan; Lu Meng; Ali Mamtimin; Huoqing Li; Xinghua Yang (Theoretical and Applied Climatology, 2020)

Relationship between air temperature and horizontal sand-dust flux observed in the Taklimakan Desert, China - Chenglong Zhou; Ali Mamtimin; Honglin Pan; Fan Yang; Wen Huo; Lu Meng; Lili Jin; Xinghua Yang (Theoretical and Applied Climatology, 2019)

Dust uplift potential in the Taklimakan Desert: an analysis based on different wind speed measurement intervals - Chenglong Zhou; Ali Mamtimin; Fan Yang; Wen Huo; Minzhong Wang; Honglin Pan; Qing He; Lili Jin; Xinghua Yang (Theoretical and Applied Climatology, 2019)

In situ Pb-Pb isotopic dating of sulfides from hydrothermal deposits: a case study of the Lala Fe-Cu deposit, SW China - Wei Terry Chen; Mei-Fu Zhou; Xiaochun Li; Jian-Feng Gao; Zhian Bao; Honglin Yuan (Mineralium Deposita, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Comparison of approaches for calculating the threshold velocity for sand movement based on field experiments in Xinjiang, China - Chenglong Zhou; Qing He; Wen Huo; Fan Yang; Ali Mamtimin; Pan Honglin; Xinghua Yang (Arabian Journal of Geosciences, 2018)

Spatiotemporal pattern of gross primary productivity and its covariation with climate in China over the last thirty years - Yitong Yao; Xuhui Wang; Yue Li; Tao Wang; Miaogen Shen; Mingyuan Du; Honglin He; Yingnian Li; Weijun Luo; Mingguo Ma; Yaoming Ma; Yanhong Tang; et al. (Global Change Biology, 2018)
The uncertainties of China's gross primary productivity ( GPP ) estimates by global data‐oriented products and ecosystem models justify a development of high‐resolution data‐oriented GPP dataset over China. We applied a machine learning algorithm developing a new GPP dataset for China with 0.1° spatial resolution and monthly temporal frequency based on eddy flux measurements from 40 sites in China and surrounding countries, most of which have not been explored in previous global GPP datasets. According to our estimates, mean annual GPP over China is 6.62 ± 0.23 PgC/year during 1982–2015 with a clear gradient from southeast to northwest. The trend of GPP estimated by this study (0.020 ± 0.002 PgC/year 2 from 1982 to 2015) is almost two times of that estimated by the previous global dataset. The GPP increment is widely spread with 60% area showing significant increasing trend ( p GPP magnitudes but underestimated the temporal trend of GPP . The monsoon affected eastern China, in particular the area surrounding Qinling Mountain, seems having larger contribution to interannual variability ( IAV ) of China's GPP than the semiarid northwestern China and Tibetan Plateau. At country scale, temperature is the dominant climatic driver for IAV of GPP . The area where IAV of GPP dominated by temperature is about 42%, while precipitation and solar radiation dominate 31% and 27% respectively over semiarid area and cold‐wet area. Such spatial pattern was generally consistent with global GPP dataset, except over the Tibetan Plateau and northeastern forests, but not captured by most ecosystem models, highlighting future research needs to improve the modeling of ecosystem response to climate variations.

Exposure to soil, house dust and decaying plants increases gut microbial diversity and decreases serum immunoglobulin E levels in BALB /c mice - Dongrui Zhou; Honglin Zhang; Zhimao Bai; Aidi Zhang; Futian Bai; Xing Luo; Yue Hou; Xiao Ding; Beili Sun; Xiao Sun; Ning Ma; Cuifen Wang; et al. (Environmental Microbiology, 2016)
Summary To assess the impact of sanitation of a living environment on gut microbiota and development of the immune system, we raised BALB /c mice under three distinct environmental conditions: a specific pathogen‐free animal room ( SPF ), a general animal room ( XZ ) and a farmhouse ( JD ). All other variables like diet, age, genetic background, physiological status and original gut microbiota were controlled for in the three groups. Using high‐throughput sequencing of the 16S rRNA gene, we found that each mouse group had a specific structure of the gut microbial community. Groups JD and XZ harboured a significantly more diverse and richer gut microbiota than did group SPF . Bacteroidetes were significantly more abundant in groups XZ and JD than in group SPF , whereas F irmicutes showed the inverse pattern. Total serum immunoglobulin E ( IgE ) levels were significantly lower in groups XZ and JD than in group SPF . There were no significant differences in gut microbiota diversity and serum IgE concentration between groups JD and XZ , but we found higher abundance of dominant genera in the gut microflora of group JD . We conclude that exposure to soil, house dust and decaying plant material enhances gut microbial diversity and innate immunity. Our results seem to provide new evidence supporting the hygiene hypothesis.

Partitioning Climatic and Biotic Effects on Interannual Variability of Ecosystem Carbon Exchange in Three Ecosystems - Junjiong Shao; Xuhui Zhou; Honglin He; Guirui Yu; Huimin Wang; Yiqi Luo; Jiakuan Chen; Lianhong Gu; Bo Li (Ecosystems, 2014)

Polymorphism of follicle stimulating hormone beta (FSHβ) subunit gene and its association with litter traits in giant panda - Xiaoyu Huang; Desheng Li; Jiwen Wang; Yan Huang; Chunchun Han; Guiquan Zhang; Zhi Huang; Honglin Wu; Ming Wei; Guosong Wang; Haiping Hu; Tao Deng; et al. (Molecular Biology Reports, 2013)

FoxM1 Involvement in Astrocyte Proliferation after Spinal Cord Injury in Rats - Shuangwei Zhang; Honglin Teng; Qiulei Ding; Jinpeng Fan; Wanying Shi; Yan Zhou; Chunwu Zhang (Journal of Molecular Neuroscience, 2013)

Targeted editing of goat genome with modular-assembly zinc finger nucleases based on activity prediction by computational molecular modeling - Kai Xiong; Shanshan Li; Hongxiao Zhang; Ye Cui; Debing Yu; Yan Li; Wenxing Sun; Yingying Fu; Yun Teng; Zhi Liu; Xiaolong Zhou; Peng Xiao; et al. (Molecular Biology Reports, 2013)

Modification of the lithospheric mantle by melt derived from recycled continental crust evidenced by wehrlite xenoliths in Early Cretaceous high-Mg diorites from western Shandong, China - QunJun Zhou; WenLiang Xu; DeBin Yang; FuPing Pei; Wei Wang; HongLin Yuan; Shan Gao (Science China Earth Sciences, 2012)

Preparation of a genipin blue from egg protein and genipin - Dan Yang; Min Zhou; Wanxing Wei; Honglin Zhu; Xiwang Fan (Natural Product Research, 2012)

Isolation and X-ray crystal structure of a securinega-type alkaloid from Phyllanthus niruri Linn - Min Zhou; Honglin Zhu; Kuiwu Wang; Wanxing Wei; Yong Zhang (Natural Product Research, 2012)

Types and spatial combinations of Danxia landform of Fangyan in Zhejiang Province - Jie Ouyang; Cheng Zhu; Hua Peng; Jinbiao Yu; Lan Li; Riliang Zhou; Guangsheng Zhang; Guangyao Zhu; Zhongxuan Li; Yishun Zhong; Qing Zhu; Wen Lv; et al. (Journal of Geographical Sciences, 2009)

Age and genesis of the Danxia landform on Jianglang Mountain, Zhejiang Province - Cheng Zhu; Hua Peng; Zhongxuan Li; Guangsheng Zhang; Lan Li; Jinbiao Yu; Guangyao Zhu; Jie Ouyang; Yishun Zhong; Qing Zhu; Shuqin Zhou; Chaogui Zheng; et al. (Journal of Geographical Sciences, 2009)